2001
DOI: 10.3354/meps222227
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of radiocesium in a marine piscivorous fish

Abstract: Radiocesium is the only trace element apart from Hg that may be potentially biomagnified at the top of the marine planktonic food chain. We quantified the assimilation efficiency from ingested prey, uptake rate from the aqueous phase, and efflux rate of radiocesium in a marine piscivorus fish (the mangrove snapper Lutjanus argentimaculatus). Aqueous 137 Cs exhibited an approximately linear uptake pattern over a 4 d exposure period, and was immediately transported to the muscles. The calculated uptake rate cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 29 publications
5
65
0
Order By: Relevance
“…Among the many elements studied so far, the AE of MeHg and radiocesium in fishes are the highest (Ni et al 2000, Zhao et al 2001, Baines et al 2002. For example, the AE of radiocesium range between 78 and 95% in the marine mangrove snappers Lutjanus argentimaculatus (Zhao et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many elements studied so far, the AE of MeHg and radiocesium in fishes are the highest (Ni et al 2000, Zhao et al 2001, Baines et al 2002. For example, the AE of radiocesium range between 78 and 95% in the marine mangrove snappers Lutjanus argentimaculatus (Zhao et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the major differences in the AE and in elimination between MeHg and Hg(II), the biomagnification of MeHg (TTF > 1) is probably caused principally by very efficient assimilation of the prey, even though the elimination rate constant is consistently low. Similarly, the potential biomagnification of radiocesium with a predicted mean TTF of 2.0 (Zhao et al 2001) resulted from a very high AE, although its elimination rate constant was fairly comparable to that of metals such as Cd, Se, and Zn.Although most bioaccumulation studies on the biomagnification of MeHg assume the Hg species is accumulated in fishes mainly in the dietary phase (e.g. by trophic transfer), there is little experimental evidence on the relative importance of aqueous vs dietary uptake under environmentally relevant exposure regimes (Hall et al 1997).…”
mentioning
confidence: 99%
“…The assimilation efficiency (AE) indicates the fraction of ingested metal remaining in the fish body after the undigested materials are evacuated. Many studies have determined the AEs of different metals in a wide range of aquatic organisms, including fish (Reinfelder and Fisher 1994;Zhao et al 2001;Long and Wang 2005). However, mechanisms underlying the dietary assimilation of metals in marine fish are not yet clearly understood.…”
mentioning
confidence: 99%
“…Previous works suggested that radiocesium is the only trace element apart from Hg that may be potentially biomagnified along food chains (Harmelin-Vivien et al, 2012;Heldal et al, 2003;Zhao et al, 2001). In our study, the modeled TTFs were generally higher than the unity for all zooplankton groups, showing evidence of biomagnification potential at this trophic level.…”
Section: Trophic Transfer Factormentioning
confidence: 99%
“…Rates of both radionuclide uptake and loss are known to be affected by species metabolism, and it has been reported that a large part of the radionuclides accumulated by heterotrophic marine biota comes from food (Thomann, 1981;Kasamatsu and Ishikawa, 1997;Zhao et al, 2001;Rowan, 2013). Therefore, the characterization of the radionuclide distribution in these components should be accompanied by ecological information such as species composition in the ecosystem, population densities, rates of primary and secondary production, food ingestion rate, etc.…”
Section: Introductionmentioning
confidence: 99%